Development of a Molecularly Imprinted Polymer for Determination of Atenolol Based on Selective Solid Phase Extraction and Application in Pharmaceutical Samples - Omaish, Hamsa Shakir; Al-Bayati, Yehya Kamal (Iraqi Journal of Science, 2024)
This paper demonstrates the synthesis and storage of molecular-imprinted polymers (MIP) at room temperature using bulk polymerization of atenolol (Ate), which is characterized by high sensitivity, low costs, and high stability. The research used 0.99:6:20 mmol ratios of template, monomer, and cross-linking agents for the polymerization in order to ensure an appropriate adsorption capacity. By making MIP for atenolol as Ate-MIP, which could be looked at with a UV-VIS spectrophotometer at 276 nm, Fourier- transform infrared spectroscopy (FT-IR), and scanning electron microscopy (SEM), a functional monomer of allyl chloride with cross-linking ethylene glycol dimethyl acrylate was made. Mass spectrometric (MS) detection may use allyl chloride to determine atenolol levels in pharmaceutical preparations. The GC/MS methods developed in this study are accurate, sensitive, and precise and can be easily applied to (NOVATEN/India and ATENOIOI/U.K.) tablets in pharmaceutical preparation. The elution process was applied to the template (Ate) from the Ate-MIP, which developed cavities, caused by using porogenic solutions of methanol, chloroform, and acetic acid (70:20:10, respectively). The maximum adsorption capacity of Ate-MIP was 2.9957 µmol/g, and the ratio of template to monomer was 1:1 in adherence to the Langmuir isotherm model. A solid-phase extraction (SPE) syringe packed with molecular imprinted polymers (MIPs) was used to selectively separate and pre-concentrate Ate from aqueous solutions and estimations of atenolol.